1998
DOI: 10.1021/np970555g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (±)-Cassumunins A and B, New Curcuminoid Antioxidants Having Protective Activity of the Living Cell against Oxidative Damage

Abstract: A chemical synthesis of cassumunins A (1) and B (2), natural curcuminoid antioxidants, was developed. The synthesis was started from o-vanillin and after nine reaction steps resulted in 20% and 26% overall yields of 1 and 2, respectively. The synthetic cassumunins showed stronger protective activity than curcumin against oxidative cell death induced by hydrogen peroxide in a rat thymocyte system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…There are many compounds having the MW greater than 500, but still have medicinal importance and used as drug. Anti-oxidant property of cassumunins A and B is well reported in the literature (Nagano et al 1997;Masuda et al 1998). Total solvent accessible surface area (SASA in Å 2 ) was calculated using a probe with a 1.4 Å radius.…”
Section: Principal Descriptors and Admet Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…There are many compounds having the MW greater than 500, but still have medicinal importance and used as drug. Anti-oxidant property of cassumunins A and B is well reported in the literature (Nagano et al 1997;Masuda et al 1998). Total solvent accessible surface area (SASA in Å 2 ) was calculated using a probe with a 1.4 Å radius.…”
Section: Principal Descriptors and Admet Analysismentioning
confidence: 84%
“…Similarly, curcumin congeners such as piperine, caffeic The anti-oxidative effects of cassumunins A and B were compared with those of curcumin and it was found that cassumunins A and B are more anti-oxidant than curcumin (Nagano et al 1997). Cassumunins A and B have shown stronger protective activity than curcumin against oxidative cell death induced by hydrogen peroxide in a rat (Masuda et al 1998). Docking study also suggests that cassumunins A and B may be more potent inhibitors of b-A aggregation than curcumin.…”
Section: Structural Conservation Of B-amentioning
confidence: 99%
“…37 As illustrated in Scheme 1, the conjugation of 1 or 2 with flutamide-related analogs, utilized 2-bromo-2-methyl propanoic acid, which was reacted with 4-substituted-3-trifluoromethylphenylamines ( 3a-e ) in the presence of EDCI and DMAP to give corresponding amides ( 4a-e ) in 30-65% yields. Reaction of these amides with 1 or 2 in the presence of anhydrous cesium carbonate (sodium iodide was used as the catalyst for making 5 and 10 ) gave the desired compounds 5 - 12 ( 2-10% yields) (Scheme 1), along with the recovered starting materials ( 1 or 2 ) (recovery rates: 39%-92%).…”
Section: Resultsmentioning
confidence: 99%
“…Excess 2,4-pentanedione or ethyl 4-acetyl-5-oxo-hexanoate was used to avoid aldol condensation occurring at both terminals of the starting material and to produce the monoaryl intermediate 16a or 17a . 10 The intermediates were subsequently condensed with an appropriate second benzaldehyde to give the target compounds 16 and 17 .…”
Section: Chemistrymentioning
confidence: 99%
“…Symmetric curcumin analogues, including 20 – 23 , 29 , 31 , and 33 – 37 with varied substituents on the phenyl rings, were then synthesized by the general synthetic pathway shown in Scheme 5. 2,4-Pentanedione or ethyl 4-acetyl-5-oxo-hexanoate was condensed with an appropriately substituted benzaldehyde in EtOAc at 70 °C using a slightly modified method of Pederson et al 12 Boric anhydride was used to form a boron complex with 2,4-pentanedione or ethyl 4-acetyl-5-oxo-hexanoate in order to prevent Knoevenagel condensation 10 (Scheme 5). …”
Section: Chemistrymentioning
confidence: 99%